Proceedings of the 2008 ACM SIGGRAPH Symposium on Video Games 2008
DOI: 10.1145/1401843.1401853
|View full text |Cite
|
Sign up to set email alerts
|

Using Greenfoot and games to teach rising 9th and 10th grade novice programmers

Abstract: In a two-week residential game camp we used the Greenfoot IDE to teach java programming to rising 9 th and 10 th graders. Students created their own computer games which required learning how to write java programs, create a game design, and create art assets. In this paper we focus on the computer science pedagogy used and describe the initial design of an augmented game development framework for the Greenfoot environment. This framework includes classes for the following useful game elements: Animation, Proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Several studies with Greenfoot have reported positive results, starting with 9th and 10th grade students in a two week game camp [18] and including even first year higher education students attending their first computing programming course based on labs and a capstone project utilizing Greenfoot [19]. However, the literature on utilizing Greenfoot as a tool for learning game programming or a tool for implementing SGs is much more limited.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies with Greenfoot have reported positive results, starting with 9th and 10th grade students in a two week game camp [18] and including even first year higher education students attending their first computing programming course based on labs and a capstone project utilizing Greenfoot [19]. However, the literature on utilizing Greenfoot as a tool for learning game programming or a tool for implementing SGs is much more limited.…”
Section: Related Workmentioning
confidence: 99%
“…Our goal is to get students excited about programming and the possibility of studying computer science by taking subsequent courses in high school and/or college. In a recent paper [1] we describe our specific programming approach and programming topics covered in more detail. In 2008 we shifted our focus and targeted our camp marketing toward young women.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, object members are added to keep track of game counters such as timers and the number of objects remaining in the game. A more detailed description of our programming approach and some utility classes we added to Greenfoot to make game programming a bit easier can be found in [1].…”
Section: Game Camp Curriculummentioning
confidence: 99%
“…Over the last two decades, several tools for supporting the process of teaching or learning programming have appeared. Tools like BlueJ [3][4][5], Alice [6,7], DrScheme [8][9][10], Greenfoot [11][12][13] or Academic Java [14] address programming in their own unique way. For example, while both BlueJ and Alice target novices in object-oriented programming, BlueJ is based on UML and Java, while Alice uses a built-in drag-and-drop interface to program a 3D world with a high degree of interaction.…”
Section: Introductionmentioning
confidence: 99%